Air Sacs Of Kuttanad Ducks (Anas Platyrhynchos Domesticus): Contrast Radiographic And Corrosion Casting Study (Applied Biological Research, 2016)
The ability of birds to sustain flight and fly in thin air of high altitude is striking evolutionary  accomplishments. The extensive anatomical plan of the lung air-sac system of birds is responsible  to achieve these accomplishments to which air sacs do play a vital role. A significant difference  exists among the birds in these air sacs as seven air sacs in goose (Onuk et al., 2010), nine in rock  partridge (Kurtul et al., 2004). Present work was aimed to castigate the occurrence of air sacs in  Kuttanad duck and find any variation exists with rest of birds.
Keywords: Kuttanad; Radiographic; Platyrhynchos